1998
DOI: 10.1093/ajcn/67.4.748s
|View full text |Cite
|
Sign up to set email alerts
|

Trends in breakfast consumption for children in the United States from 1965-1991

Abstract: We examined breakfast consumption patterns and trends between 1965 and 1991 for children (1-10 y old) and adolescents (11-18 y old) in the United States. The analysis was undertaken by pooling nationally representative samples obtained from the Nationwide Food Consumption Surveys of 1965 and 1977-1978 and the 1989-1991 Continuing Survey of Food Intakes by Individuals. Breakfast consumption, defined as the consumption of food, beverage, or both between 0500 and 1000, was the focus of the trends analysis. Descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
243
4
26

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(292 citation statements)
references
References 19 publications
19
243
4
26
Order By: Relevance
“…This finding is consistent with other studies in which breakfast skipping in adolescents has also been associated with various health-compromising behaviours and unhealthy lifestyles (20)(21)(22)(23) . Other studies have also shown that breakfast skippers, even after controlling for age, gender and BMI, have significantly higher total cholesterol levels than breakfast consumers.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with other studies in which breakfast skipping in adolescents has also been associated with various health-compromising behaviours and unhealthy lifestyles (20)(21)(22)(23) . Other studies have also shown that breakfast skippers, even after controlling for age, gender and BMI, have significantly higher total cholesterol levels than breakfast consumers.…”
Section: Discussionsupporting
confidence: 93%
“…An analysis of national food consumption surveys from 1965-1991, found a decline in breakfast consumption over the 25 years especially among adolescents, 74.9% to 64.7% (Siega-Riz, Popkin, & Carson, 1998). This decline is worrisome because studies have found a possible positive role for breakfast consumption in maintaining normal weight in children and adolescents (Rampersaud, Pereira, Girard, Adams, & Metzel, 2005).…”
Section: Meal Patterns and Dietary Intakementioning
confidence: 99%
“…Missing breakfast has also been associated with decreases in attention, memory and school performance (5,6) , all important factors in children's development. In addition, there are indications that breakfast patterns are linked to overweight and obesity (7)(8)(9)(10)(11)(12) . It is of concern that a decline in breakfast consumption has been observed in recent years.…”
mentioning
confidence: 99%